Thermal process of Aw-controlled sweet white kidney beans (Phaseolus vulgaris) packed in glass jars - Lulu, Maria Carmen Gandionco 1961- (2004)
This study was conducted to establish a scientific basis for thermal process of a aw-controlled sweet white kidney beans in 12 ounce glass jar to achieve commercial sterility. Varying levels of sucrose were added to the different treatments, resulting in total soluble solids ranging from 40 to 55°BX. The sucrose added effectively controlled the aw of the products within the desired range, 0.89 to 0.93. The products were confirmed to be low-acid with pH values ranging from 5.9 to 6.18. The thermal Death Time (TDT) parameters of the test organism, Staphylococcus aureus, and a reference organism, Clostridium sporogenes PA 3679, were determined. S. aureus had a D80°C of 0.9 minute and a z of 15°C while PA had 24 minutes and 13.5°C, respectively. PA 3679 had D100°C values of 2.07, 1.65, 1.15 and 0.5 minutes, z values of 16, 15.5, 14 and 13.5°C for formulations having aw values of 0.93, 0.92, 0.91 and 0.89, respectively. TDT tests using PA 3679 in different formulations of sweet white kidney beans showed that the heat resistance of reference microorganism increased with decreasing aw. Heat penetration tests to simulate the actual commercial practice of the local food processors revealed that increasing the initial temperature (IT) prior to heat processing decreased the process times required for the different formulations. Sensory evaluation of the processed products revealed that the 50°Bx formulation had the best overall sensory qualities. Process time required for his formulation is 42 minutes at 100°C with an IT of 35°C.